STUDY OF ANALYSIS OF CHILD VICTIMS OF CRIME PROTECTION IN A VICTIMOLOGICAL PERSPECTIVE - Marzuki Marzuki (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
This research aims to improve the protection of children of crime victims, which often occurs when the provision of services to children who are temporary or permanent victims of psychological, physical and social suffering is neglected. It is a study to analyze from the viewpoint of victimology.The specification or type of research in this research is descriptive in nature and uses prescriptive legal research methods through several approaches.The statutory regulatory approach (statutory approach) and the conceptual approach (conceptual approach).Investigations have shown that various laws have been adopted as legal policies to implement the constitutional provisions of the 1945 Constitution of the Republic of Indonesia, including Presidential Decree No. 36 of 1990 on ratification, in order to protect children in conflict with the law. It is shown that the regime has emerged. Convention on the Rights of the Child (Convention on the Rights of the Child), Law No. 4 of 1979 on Child Welfare, Law No. 8 of 1981 on Criminal Procedure Code, Law No. 39 of 1997 on Juvenile Courts, Law No. 39 of 1999 on Human Rights, Law No. 23 of 2014 on Amending Law No. 23 of 2002 on Child Protection and Law No. 35 of 2014 on Juvenile Criminal Justice System Law No. 11 Including children in conflict with the law to provide legal protection as both perpetrators and victims. In light of these various legal systems, the police, prosecutors, and judges in the law enforcement agency (prosecutor's office) always strive to provide children with the best progressive laws for children in line with the concept of juvenile justice for children. It must be the embodiment of teaching, nurturing and protection of Prioritize the application of restorative justice and diversion to ensure that victims' rights are not ignored, and protect child victims of crime from a victimological perspective.In summary, the legal protection of children of crime victims in Indonesia entitles them to various rights, including: B. Losses such as the right to compensation, the right to treatment, the right to be intimidated by the perpetrator, the right to counseling and rehabilitation, especially the perpetrator's inability to pay compensation to the victim due to the existence of the Victim Compensation Office. case .